STUDY OF UTERINE ASPIRATION CASES IN PATIENTS OVER 45 YEARS OLD WITH SUSPECTED ENDOMETRIAL PATHOLOGY (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of endometrial histopathological lesion types and analyze some related factors in women aged 45 years and older.Subjects and Methods: A cross-sectional descriptive study was conducted on 299 patients aged 45 and older with suspected endometrial pathology who underwent uterine aspiration at Nghe An Obstetrics and Pediatrics Hospital from January 2023 to December 2024.Results: Among 299 cases, the rate of no lesions was 71.2%. In the group with lesions (n=86), benign lesions accounted for 69.8% (mainly typical endometrial hyperplasia), while cancer and precancerous lesions accounted for 30.2% (including endometrial cancer and atypical endometrial hyperplasia). Multivariate analysis showed that independent factors increasing the risk of malignant/premalignant lesions included: early menarche
Keywords: Endometrium, uterine aspiration, endometrial hyperplasia, endometrial cancer, menopause.